Experimental and simulated demonstration of a theoretical model for dip-type spectral sidebands in soliton fiber lasers. (September 2021) - Wu, Qianchao; Liu, Chuyan; Yao, Yong; Wu, Chonghao; Xu, Xiaochuan; Yang, Yanfu; Tian, Jiajun; Xu, Ke
Highlights: The generation and evolution mechanism of dip-type sidebands (DS) was revealed. A theoretical model that can predict the positions of DS was proposed. The mathematical expression of DS was strictly deduced. The reliability of the theoretical model is verified by experiments and simulations. Abstract: The formation and evolution of dip-type spectral sidebands are numerically and experimentally researched in a soliton fiber ring laser passively mode locked by the nonlinear polarization rotation (NPR) technique. We provide a theoretical model that can predict the positions of dip-type sidebands, and point out that the formation of the dip-type sidebands is due to the local destructive interference effect between the soliton and dispersive waves induced by the periodic soliton perturbations in the laser cavity. The expression describing the position of dip-type sidebands is strictly deduced, which indicates that the positions of dip-type sidebands on the spectrum can be changed with the pulse width variation. The reliability of the theoretical model of dip-type sidebands is verified by experiments and simulations; both the experimental observations and numerical simulations can well confirm the theoretical predictions.